Writing sensation: Deleuze, literature, architecture and Virginia Woolf's The Waves. Issue 1 (2nd January 2016) - Jobst, Marko
Abstract : This essay poses the question of how to write architecture. It uses as example the writing of Virginia Woolf in the novel The Waves, aiming to show that Woolf employs a particular mode of rendering architecture through sensory means, which in turn offers a way of discussing approaches to writing architecture that are not often foregrounded in architectural discourse. This is elaborated in the context of the philosophy of Gilles Deleuze, which offers a useful set of conceptual tools through the notions of percept and affect, and, more specifically, the 'visions and auditions' pertinent to language. The aim is to show that we can learn from writing methods such as Woolf'oo both as observers/thinkers in architecture and as writers attempting to recast its material presence in language, while simultaneously developing a finer conceptual palette derived from philosophy.